(-4)+(-7)=(-7)+? answer fastt ​

Question

(-4)+(-7)=(-7)+?

answer fastt ​

in progress 0
Kinsley 3 weeks 2021-08-23T00:32:14+00:00 2 Answers 0 views 0

Answers ( )

  1. Ava
    0
    2021-08-23T00:33:18+00:00

    Answer:

    ( - 4) + ( - 7) = ( - 7) + ( - 4) \\  - 11 =  - 11

    Hope it helps you

    Mark as brainliest (✷‿✷)

  2. Ava
    0
    2021-08-23T00:33:37+00:00

    Solution

    Let’s keep the unknown value be “x”

    \implies \:  - 4 + ( - 7) = ( - 7) + x

    \implies \:  - 11 =   \:  - 7 + x

    \implies \:  - 11 + 7 = x

    \implies \: x =  - 4

    To check:

    \implies \:  - 4 + ( - 7) = ( - 7) + x

    \implies \:  - 4 + ( - 7) = ( - 7) + ( - 4)

     - 11 = ( - 11)

    Therefore, hence verified.

    Hope it helps you…

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )